Evolution of the canonical sex chromosomes of the guppy and its relatives. Issue 2 (21st December 2021) - Kirkpatrick, Mark; Sardell, Jason M; Pinto, Brendan J; Dixon, Groves; Peichel, Catherine L; Schartl, Manfred
Abstract: The sex chromosomes of the guppy, Poecilia reticulata, and its close relatives are of particular interest: they are much younger than the highly degenerate sex chromosomes of model systems such as humans and Drosophila melanogaster, and they carry many of the genes responsible for the males' dramatic coloration. Over the last decade, several studies have analyzed these sex chromosomes using a variety of approaches including sequencing genomes and transcriptomes, cytology, and linkage mapping. Conflicting conclusions have emerged, in particular concerning the history of the sex chromosomes and the evolution of suppressed recombination between the X and Y. Here, we address these controversies by reviewing the evidence and reanalyzing data. We find no evidence of a nonrecombining sex-determining region or evolutionary strata in P. reticulata. Furthermore, we find that the data most strongly support the hypothesis that the sex-determining regions of 2 close relatives of the guppy, Poecilia wingei and Micropoecilia picta, evolved independently after their lineages diverged. We identify possible causes of conflicting results in previous studies and suggest best practices going forward.